The impact of social media influencers’ bragging language styles on consumers’ attitudes toward luxury brands: The dual mediation of envy and trustworthiness - Feng, Wenting; Chang, Dihui; Sun, Hongjie (Frontiers in Psychology, 2023)
On social media, luxury brand managers often use influencers’ bragging language as a marketing tool. As modesty is considered a virtue in the Chinese context, Chinese influencers tend to adopt a humblebragging language style. Research has examined the impact of bragging language styles on luxury brands and has found that humblebragging, which appears to be modest, has a negative influence on brand attitudes. From the perspective of social comparison theory, we proposed a dual mediation model of malicious envy and trustworthiness to reveal the internal mechanisms and moderating factors of the negative effects of humblebragging. The results of three experiments indicated that compared with straightforward bragging, humblebragging was more likely to elicit malicious envy and lower levels of trust in an influencer, resulting in negative attitudes toward the luxury brand endorsed. Moreover, this negative effect was stronger when the influencer lacked expertise or had high similarity with consumers. Our findings enrich the antecedents of social media influencer marketing and provide managers with implications for maximizing the effectiveness of influencer marketing by matching influencers with word-of-mouth content.